STRATEGI PENINGKATAN PENDAPATAN PETANI DI KENAGARIAN GUGUAK VIII KOTO, KECAMATAN GUGUAK, KABUPATEN LIMA PULUH KOTA PERSPEKTIF EKONOMI ISLAM - Taufik Hidayat; Khadijah Nurani (CV. Adiba Aisha Amira, 2023)
Rice farming as a food commodity and also as the main source of income for the community in Kenagarian Guguak VIII Kot, makes the agricultural sector the majority occupation occupied by the people in the area. As the main income, of course, it is undeniable that it experiences fluctuations as a result of problems and threats that come. The purpose of this research is to formulate the right strategy to increase farmer’s income in Kenagarian Guguak VIII koto. this type of research is to qualitative research through a descriptive qualitative approach. This research requires data obtained from interviews and field observations with rice farmers and toke in Kenagarian Guguak VIII koto. The results of this study in formulating strategies to increase farmers' income in Kenagarian Guguak VIII Koto by exploiting existing opportunities by minimizing their weaknesses. Where possible strategies to be implemented are alternative fertilizer substitutes in overcoming limitations, improving agricultural facilities and infrastructure, and creating new irrigation